Content Analysis Of Undergraduate Guiding Documents For A Medical Graduate Attributes In Different Healthcare Systems - Baseer, Najma; Huma, Zilli; Habib, Syed Hamid; Mehboob, Usman (ADVANCES IN BASIC MEDICAL SCIENCES, 2019)
Objective The basic aim of this study is to compare and assess the attributes/competencies presented in the publically available guiding documents of globally accepted healthcare systems and accreditation bodies. Methods A thematic and manifest content analysis of six such documents was done to determine the commonalities and differentiating features among the attributes of different medical graduates all over the globe. Six common attributes and several sub-attributes were identified through thematic analysis and later searched in the documents using the Ctrl+F option. The data was plotted on MS Excel sheet and the percentage frequencies were deduced. Results The results suggested that the two attributes that received the major emphasis were clinical/applied skills and knowledge. Among the remaining four, professionalism, personal grooming and leadership showed a mixed pattern while the community healthcare was mentioned minimally. Conclusion This study suggests that globally, undergraduate guiding documents of the major healthcare systems expect their medical graduates to acquire almost similar attributes at the culmination of their respective degrees. However, the amount of emphasis laid on them by these healthcare systems may vary depending upon their local needs. Interestingly, the attributes delineated by Pakistan Medical & Dental Council are in considerable alignment to the ones recognized globally.